Biochemical and molecular characterisation of neurological Wilson disease. Issue 9 (4th April 2018) - Seo, Go Hun; Kim, Yoon-Myung; Oh, Seak Hee; Chung, Sun Ju; Choi, In Hee; Kim, Gu-Hwan; Yum, Mi-Sun; Choi, Jin-Ho; Kim, Kyung Mo; Ko, Tae-Sung; Lee, Beom Hee; Yoo, Han-Wook
Abstract : Background: To identify biochemical and genetic features that characterise neurological Wilson disease as a distinct disease subgroup. Methods: Detailed biochemical profiles and genotypic characteristics of neurological (86 patients) and hepatic subgroups (233 patients) from 368 unrelated Korean families were analysed. Results: Compared with patients in the hepatic subgroup, patients in the neurological subgroup had a later age at onset, a higher proportion with Kayser-Fleischer rings and higher serum creatinine levels, and a lower proportion with favourable outcome (62% vs 80%, P<0.016). At diagnosis, the neurological subgroup had lower serum ceruloplasmin (3.1±2.1 mg/dL vs 4.2±3.2 mg/dL, P<0.001), total copper (26.4±13.8 µg/dL vs 35.8±42.4 µg/dL, P=0.005), free copper (17.2±12.5 µg/dL vs 23.5±38.2 µg/dL, P=0.038) and urinary copper (280.9±162.9 µg/day vs 611.1±1124.2 µg/day, P<0.001) levels. Serum aspartate aminotransferase, alanine aminotransferase, gamma glutamyltransferase and total bilirubin levels, as well as prothrombin time, were also lower in the neurological subgroup. Liver cirrhosis was more common but mostly compensated in the neurological subgroup. Frameshift, nonsense or splice-site ATP7B mutations and mutations in transduction or ATP hinge domains (2.4% vs 23.1%, P=0.006) were less common in the neurological subgroup. Conclusion: The neurological subgroup had distinct clinical, biochemical and genetic profiles. Further studies are required to identify the factors, with or without association with copper metabolism, underlying the neurological presentation for which treatment needs to be targeted to improve the clinical outcome of this subgroup.